Applying a large-scale device using non-thermal plasma for microbial decontamination on shell eggs and its effects on the sensory characteristics. (May 2021) - Lin, Chia-Min; Herianto, Samuel; Syu, Shih-Ming; Song, Cian-Huei; Chen, Hsiu-Ling; Hou, Chih-Yao
Abstract: Concerns related to foodborne pathogens such as Salmonella enterica serovar Enteritidis (SE) necessitate the decontamination of eggs. Multiple studies have successfully demonstrated the use of non-thermal plasma (NTP) technology in inactivating SE on artificially inoculated shell eggs. However, the NTP devices abovementioned were operated in the batch mode and small scale. The present study is the first attempt to evaluate the effectiveness of a large-scale device using NTP for egg decontamination. The designed NTP was operated at 400 W (power), 30 slm (Ar flow rate), 5 and 10 eggs/min (speed of conveyor belt), and 4 cm (distance between the plasma jets and egg samples). Conducting a two-round treatment for the egg samples at 400 W-30 slm-5 eggs/min-4 cm achieved the highest reduction of SE populations (3.57 log CFU/egg). SEM observation revealed less damage on the surface of the plasma-treated eggs than the commercial-washed eggs. Overall, NTP treatment can maintain the freshness quality and sensory characteristics until 15-day storage. This study demonstrated a large-scale NTP system was able to effectively achieve a significant reduction of pathogenic SE without adversely affecting egg quality properties. These results suggested the readiness of this NTP device for industrial applications. Graphical abstract: Image 1 Highlights: First research to apply a large-scale non-thermal plasma in egg decontamination. This effectively reduced Salmonella Enteritidis on egg surface up to 3.57 log CFU/egg. Egg quality traits and sensory properties were not compromised. This work suggests its readiness for industrial applications.